Analisis Pengaruh Audit Capacity Stress, Audit Tenure, dan Skeptisisme Terhadap Kualitas Audit - Aurellia Thifaal Harfa Sabela,; Rifqi Muhammad, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research focuses on factors that can influence audit quality, namely audit capacity stress, audit tenure, and skepticism. The aim is to investigate the impact of audit capacity stress, audit tenure, and skepticism on audit quality among auditors at KAP Y. Involving 32 auditor respondents, primary data was collected through questionnaires and analyzed using SPSS software. Data analysis indicates that audit capacity stress does not have a significant influence on audit quality. Similarly, audit tenure does not show a significant impact on audit quality. However, regarding skepticism, the auditor's level of skepticism has been proven to have a significant influence on audit quality. This research contributes valuable insights into the internal dynamics that can affect the effectiveness of audits at KAP Y.